Effect of Irrigation Scheduling and Drought Alleviating Microbes on Growth and Yield of Indian Mustard (Brassica juncea L.) - Chaudhary, G. D.; Jat, A. L. (International Journal of Bio-resource and Stress Management, 2025)
A field experiment was conducted at Agronomy Instructional Farm, Chimanbhai Patel College of Agriculture, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar during rabi season of October, 2022 to February, 2023 to identify strategies using to improve plant growth under water deficit stress. The experiment was laid out in a split plot design with four replications, consisting of twelve treatment combinations comprising three irrigation schedules in main plot viz. 0.6 IW/CPE ratio, 0.8 IW/CPE ratio and 1.0 IW/CPE ratio and four drought alleviating microbes in sub plot viz. Control (without microbes), MRD-17, CRIDA MI-I and CRIDA MI-II. The results indicated that significantly higher growth and yield parameters viz. plant height at harvest (184.4 cm) was recorded with irrigation scheduled at 1.0 IW/CPE ratio and, CGR, RGR, dry matter accumulation at harvest (54.02, 54.20 g plant-1), number of secondary branches plant-1 (15.92 and 15.84), number of siliquae plant-1 (303.3 and 286.3), seed yield (2045 and 2018 kg ha-1), crop productivity (17.94 and 17.70 kg ha-1 day-1) with irrigation scheduled at 1.0 IW/CPE and CRIDA MI-I, individually. Number of seeds per siliqua, siliqua length, test weight and harvest index of mustard were not affected by irrigation scheduling and drought alleviating microbes. Maximum net return (`Rs. 71486 and 71999 ha-1), crop profitability (`Rs. 627 and 632 ha-1 day-1) and BCR (2.68 and 2.77) was secured with irrigation scheduled at 1.0 IW/CPE and seed inoculated with CRIDA MI - I.